Plate tectonics the puzzle of the continents - Superstone, Herb; Superstone, Herb (Fort Collins : Scott Resources Inc., 1990)
This is an 18 minutes full motion videotape that explores the scientific revolution that began with Alfred Wegener's hypothesis on continental drift and ends with today's theory of global plate techtonics. Using coloful computer graphics with exciting live action video from locations around the world ,it explains where crustal plates are found, why their interaction results in earthquakes and volcanoes, and how their perpetual movement is governed by forces deep within the earth
Keywords: Plate tectonics